Uptake and distribution of ions reveal contrasting tolerance mechanisms for soil and water salinity in okra (Abelmoschus esculentus) and tomato (Solanum esculentum) - Kamaluldeen, J.; Yunusa, I.; Zerihun, Ayalsew; Bruhl, J.; Kristiansen, P. (Elsevier, 2014)
Okra and tomatoes are major vegetable crops commonly grown under irrigation, and understanding whether they respond to salinity by withstanding (tissue tolerance) or avoiding (salt exclusion) accumulation of salt in the shoots will assist with management for optimizing yield under declining soil and water resources. Both crops were grown in non-saline (0.0 dS/m) and saline (3.0 dS/m) loamy sand and drip irrigated with water of 0.0, 1.2 or 2.4 dS/m. Differences in the growth and yields of the two crops under saline conditions were associated with uptake and distribution of cations, especially Na. The tomato employed tissue tolerance mechanism in response to salinity and produced fruits even when shoot/root Na concentration was >3.0; concentrations of Na in tomato tissues was in the order shoots > roots ≈ fruits. Okra was sensitive to shoot Na such that a shoot/root Na concentration as low as 0.13 reduced yield by as much as 35%; this crop employed salt exclusion mechanism and minimized shoot accumulation of Na, which was distributed in the order fruits > roots > shoots.Root and shoot concentrations of Na, P and S were correlated with flower abortion and negatively correlated with yield and yield components in both crops. Fresh fruit produced on the saline soil were reduced by 19% in tomato compared with 59% in okra, relative to yields on non-saline soil. Water salinity reduced fresh fruit yields in the tomato by as much as 36% with every unit (dS/m) rise in water salinity compared with 27% in okra. Soil salinity significantly reduced water-use by 6% in tomatoes and 29% in okra, but had no impact on water use efficiency (WUE) that averaged 3.9 g of fresh fruits/L for tomatoes and 1.75 g/L for okra. Every 1.0 dS/m rise in water salinity reduced water-use by 0.33 L in okra and 3.31 L in tomatoes, and reduced WUE by 2.61 g/L in tomatoes and 0.53 g/L in okra. Soil salinity explained <5% of the variance in yields in tomatoes and 10–20% in okra, while water salinity explained 48–68% of the variance in tomatoes and about 40% in okra. We conclude that (1) water salinity was more injurious to yield in both crops than soil salinity, and (2) yield losses due to salinity can be minimized through frequent leaching of soil salt under okra and increased irrigation intervals in tomatoes.